Adorning Shared Spaces - Deo, Juliana Satchell (Auckland University of Technology, 2014)
This work pursues an interest in the protocols of my own cultural traditions of the Torres Strait Islands specifically Pacific adornment and customary ritualistic practices. The scope of this work is limited to an exploration of the ilan dress and its performativity as an object. The dress is mapped as a two-dimensional object, yet to be worn. Through iterative making it is deconstructed, re-con-structed and performed as an ancestral re-telling through my grandmothers, mother, aunties, sister and my own daughters. Throughout this project I have explored many ritual practices and ancestral stories that have been passed down to me through the maternal lines in my family. I have learned to question the origins and the purpose of these traditions. Many of the answers I gathered sitting respectfully in my mother’s kitchen listening to the stories, songs and dance that began this project. What I imagined to be a straightforward study and a rite of passage turned out be one of the most humbling experiences of my academic journey. This exegesis is the story of that journey.
Keywords: Torres Strait Islands; Dress; Papua New Guinea